Persepsi Nilai dan Niat Pembelian pada Layanan Premium : Studi kepada para Gamers di Indonesia - Tri Tata Wilia; Dessy Kurnia Sari; Sari Lenggogeni (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study focuses on the perceived value of premium games among users and its impact on usage and premium content purchase intentions. The research aims to explore how social value, quality, enjoyment, and economic value influence users’ willingness to continue using the service and purchase premium content. Using an online survey method through Google Forms with 150 respondents, the study found that the higher the level of enjoyment in the premium service, the lower the intention to purchase premium content, but it strengthens the intention to continue using the service. Other findings show that social value increases both premium usage and premium purchase intentions. Additionally, service quality has a positive correlation with usage intention, but does not affect premium purchases. Overall, the results of this study highlight the unique characteristics of the premium business model in enhancing user retention through high perceived value, although challenges remain in premium monetization.